A renormalization group method for studying the early universe in the Lorentzian IIB matrix model. (1st August 2014) - Ito, Yuta; Kim, Sang-Woo; Koizuka, Yuki; Nishimura, Jun; Tsuchiya, Asato
Abstract: We propose a new method for studying the early universe in the Lorentzian version of the IIB matrix model, which is considered to be a nonperturbative formulation of superstring theory. This method is based on the idea of the renormalization group, and it enables us to study the time-evolution of the universe for a much longer time than in the [S.-W. Kim, J. Nishimura, and A. Tsuchiya, Phys. Rev. Lett. 108, 011601 (2012)], which showed that the SO(9) rotational symmetry is spontaneously broken down to SO(3) after a "critical time". We demonstrate how this method works in a simplified model, which is expected to capture the behaviors of the original model when the space is not so large. In particular, we present clear evidence that the 3D space expands exponentially after the critical time in this simplified model.